Nine-, but Not Four-Days Heat Acclimation Improves Self-Paced Endurance Performance in Females - Kirby, Nathalie V.; Lucas, Samuel J. E.; Lucas, Rebekah A. I. (Frontiers in Physiology, 2019)
Although emerging as a cost and time efficient way to prepare for competition in the heat, recent evidence indicates that “short-term” heat acclimation (<7 days) may not be sufficient for females to adapt to repeated heat stress. Furthermore, self-paced performance following either short-term, or longer (>7 days) heat acclimation has not been examined in a female cohort. Therefore, the aim of this study was to investigate self-paced endurance performance in hot conditions following 4-days and 9-days of a high-intensity isothermic heat acclimation protocol in a female cohort. Eight female endurance athletes (mean ± SD, age 27 ± 5 years, mass 61 ± 5 kg, VO2max 47 ± 6 ml⋅kg⋅min-1) completed 15-minute self-paced cycling time trials in hot conditions (35°C, 30%RH) before (HTT1), after 4-days (HTT2), and 9-days (HTT3) isothermic heat acclimation (HA, with power output manipulated to increase and maintain rectal temperature [Trec] at 38.5°C for 90-min cycling in 40°C, 30%RH) with permissive dehydration. There were no significant changes in distance cycled (p = 0.47), mean power output (p = 0.55) or cycling speed (p = 0.47) following 4-days HA, (i.e., from HTT1 to HTT2). Distance cycled (+3.2%, p = 0.01; +1.8%, p = 0.04), mean power output (+8.1%, p = 0.01; +4.8%, p = 0.05) and cycling speed (+3.0%, p = 0.01; +1.6%, p = 0.05) were significantly greater in HTT3 than in HTT1 and HTT2, respectively. There was an increase in the number of active sweat glands per cm2 in HTT3 as compared to HTT1 (+32%; p = 0.02) and HTT2 (+22%; p < 0.01), whereas thermal sensation immediately before HTT3 decreased (“Slightly Warm”, p = 0.03) compared to ratings taken before HTT1 (“Warm”) in 35°C, 30%RH. Four-days HA was insufficient to improve performance in the heat in females as observed following 9-days HA.